Data of religious thought and its reflections in modern textile designs - Asaad Ati Halil Saad Al-Moussawi (الاكاديمي)
Textiles are among the consumer products that people cannot do without, because of their utilitarian value, in addition to their aesthetic value, which expresses all aspects of society, as they are affected, like other arts, by their data Intellectual design to derive its design units from reality, and its ability to derive new design ideas resulting from the designer’s own sensitivity to the references from which design thought is derived. The research problem was determined according to the following question: What are the data of religious (Islamic) thought and its implications on the designs of modern curtain fabrics?